2014
DOI: 10.1097/cad.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of raltitrexed-based first-line chemotherapy in advanced colorectal cancer

Abstract: Raltitrexed is a thymidylate synthase inhibitor belonging to the antimetabolite class of cytotoxic drugs. It is also effective in colorectal cancer (CRC) both as a single agent and in combination with other drugs, in particular in those patients with cardiologic risk factors or previous cardiotoxicity. The efficacy of first-line raltitrexed-based chemotherapy containing oxaliplatin (TOMOX) and irinotecan (TOMIRI) was investigated in this systematic review. Studies that enrolled advanced CRC patients for first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Although the alanine aminotransferase level and bilirubin were increased, these abnormalities resolved within 5 days and did not show any relevant deterioration. The occurrence of main adverse events including biochemistry level changes and gastrointestinal adverse reactions in our study were consistent with that reported previously [20]. However, Sahara et al reported that Grade 3 transaminase elevation and hepatic artery abnormality in TACE with multiple anti-cancer drugs (epirubicin, cisplatin, mitomycin C, and 5-fluorouracil) was significantly greater than that in the epirubicin group among 63 consecutive patients who underwent TACE prospectively [7].…”
Section: Discussionsupporting
confidence: 82%
“…Although the alanine aminotransferase level and bilirubin were increased, these abnormalities resolved within 5 days and did not show any relevant deterioration. The occurrence of main adverse events including biochemistry level changes and gastrointestinal adverse reactions in our study were consistent with that reported previously [20]. However, Sahara et al reported that Grade 3 transaminase elevation and hepatic artery abnormality in TACE with multiple anti-cancer drugs (epirubicin, cisplatin, mitomycin C, and 5-fluorouracil) was significantly greater than that in the epirubicin group among 63 consecutive patients who underwent TACE prospectively [7].…”
Section: Discussionsupporting
confidence: 82%
“…Raltitrexed is a direct thymidylate synthase inhibitor belonging to the antimetabolite class of cytotoxic drugs [8]. It is has been reported to be effective in a number of tumor types both as a single agent or in combination with other drugs such as DOX and OXA [7]. Raltitrexed has been shown to have no cardiac toxicity and can potentially serve as a substitute for conventional drugs such as 5-FU [5,17].…”
Section: Safety and Toxicitymentioning
confidence: 98%
“…The first-line drugs used in TACE include fluorouracil (5-FU), doxorubicin (DOX), and oxaliplatin (OXA), and are associated with a number of adverse effects, indicating a need for an alternative agent [5]. Raltitrexed (also known as tomudex) is a quinazoline antifolate thymidylate synthase inhibitor [6] that has been shown to have anticancer effects in both preclinical and clinical studies [7][8][9][10]. Reports have shown its efficacy and safety in many tumor types including colorectal and breast cancers; however, the clinical data of raltitrexed in HCC treatment are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Raltitrexed is a direct thymidylate synthase inhibitor which has been compared with 5-FU in the metastatic setting and appears to be noninferior [51]. When raltitrexed is combined with oxaliplatin (TOMOX) in the metastatic setting, it appears to have similar efficacy to FOLFOX in both first and second line settings, but this has not been validated in the context of a large Phase III trial [52].…”
Section: • • Coronary Vasospasmmentioning
confidence: 97%